Estimation Of Postharvest Losses And Analysis Of Insecticide Residues In Some Selected Vegetable Crops In The Greater Accra Region Of Ghana - Amartey, J.N.A. (University of Ghana, 2013)
Small-scale farmers in the Greater Accra region of Ghana grow vegetable crops including tomato, cabbage, pepper, okra and garden eggs and apply many types of pesticides to control pests and diseases that attack these crops. This study was conducted in the Accra Metropolitan District, Adenta Municipal District, Ashaiman Municipal District, Dangme West District, Ga South Municipal District and Ga West Municipal District. The purpose of the study was to estimate the postharvest losses in the seleted vegetable crops incurred by the farmers and retail traders, determine pesticide use pattern of vegetable farmers and analyse specifically, the level of insecticide residues in okra sent to the market. The communities studied included Weija, Kojo Ashong, Kordeabe, Dawenya, Dzorwulu, Obaakruwa, Ashaiman, Atomic, Okushiabade and Onyaasanaa. A total of 100 farmers and 75 retailers were randomly selected for the studies. The various methods used for the study included questionnaire administration, physical observations and personal interviews. The vegetable farmers and traders were interviewed and both closed and open ended questionnaires were administered to them from November 2011 – March 2012 to assess the extent of postharvest loss and pesticide use pattern of the farmers. Okra samples from four farms namely Weija, Dawenya, Atomic and Ashaiman were sent to the Ghana Standard Authority for analysis of insecticide residues. It was confirmed that postharvest losses was a major problem experienced by vegetable crop farmers and traders. The losses were mostly caused by pests and diseases and poor handling. As a result farmers sprayed chemical pesticides to control them in order to meet market demands. From the study, percent estimated losses by farmers were 13% for cabbage and okra, 12% for pepper, 1% for eggplant, and 20% for tomato. About 15%, 7%, 8% and 10% were estimated lossess for cabbage, pepper and okra respectively. Loss for garden eggs was insignificant due to their ability to maintain their freshness till they were sold to consumers. Commonly applied insecticides included Auntie Ataa, Golan, Cydim Super, Attack; fungicides included Sulpur 80, Bendazim, Mangozeb and herbicides were Round up, Ejumawura and Paraquat. Only 5% of 100 farmers interviewed used neem extracts to control pests and diseases. Most farmers’ sprayed pesticides themselves but 10% employed skilled labour and the pesticide application was usually done in the mornings or evenings. Knowledge on the correct pesticide application was obtained from Ministry of Food and Agriculture staffs, pesticide dealers and colleague farmers. The farmers also attested to the fact that the chemical pesticides used were poisonous and caused various health hazards. Some compounds detected from the test conducted in the laboratory indicated the presence of Alpha-Endosulfan, Endrin, Fenvalerate, P,P’-DDE and Ethoprophos. The results generated indicated that the okra samples that were tested for insecticide residues were below EU’s Minimum Residue Levels (MRLs).
Thesis (MPhil)- University of Ghana, 2013